Creating a structured practice space with online mini-speeches. Issue 2 (3rd April 2017) - Gerbensky-Kerber, Anne
ABSTRACT: Courses: This semester-long assignment series was developed for an online introductory public speaking class, but it has also been used successfully in a hybrid (combination of online/face-to-face meetings) format. Objectives: Students will practice delivering speeches in an online format by applying key concepts from course materials to personal experiences. Students will engage in peer-feedback processes to encourage collaboration and interaction in the online public speaking classroom.